Family Social Support Reduces Post Judegemental Stress in Teenagers - Nursalam Nursalam; Ni Ketut Alit Armini; Rista Fauziningtyas (Universitas Airlangga, 2009)
Introduction: Justicial proceeding is able to make any stress or anxiety for everyone that through on it, especially if the process happens on teenagers. The stressor which can make stress in justicial proceeding are the justicial proceeding that doesn’t go along with UU RI No. 3 tahun 1997, i. e. children justicial process, fearness of parents and friend lost, worried about his future, and new neighborhood that is not appropriate with the child’s psychology development. The presence of family is very important to give a social support to the arrested teenagers.The objective of this study was to know the correlation between family social support and post judegement stress in teenagers and the factors of stress in teenagers. Method: This study use Cross Sectional design. Population had taken from teenagers from 13 until 17 years old. Sample was comprised in to 12 individuals who fit with the inclusion criteria. The independent variable in this study was family social support and factors of stress in teenagers, and the dependent variable was post judgement stress in teenagers. Data was collected by measurement using Mood and Feeling Questionnaire (MFQ) for stress, questionnaire of family social support, and interviewed. They were analyzed by Spearman’s test with significance level α<0.05 and content analysis for interview result. Result: The result showed that there is a correlation between family social support and post judgement stress in teenagers with significance level p=0.013.It means, Content analysis’ results showed that the factors which related with stress in teenagers are environment, caring type, interfamily member’s relationship, bad event, and characteristic of children. Discussion: Higher family social support makes teenagers have higher self esteem and more optimistic view, so the teenagers will able to face their problem.